2022
DOI: 10.1002/zaac.202100380
|View full text |Cite
|
Sign up to set email alerts
|

A caveat on the effect of modulators in the synthesis of the aluminum furandicarboxylate metal‐organic framework MIL‐160

Abstract: Modulators are widely used in the synthesis of metal-organic frameworks (MOFs) for improving the porosity and morphology. For aluminum MOFs modulation has been seldom reported and as is shown here for the example of the aluminum furandicarboxylate MOF MIL-160 the positive effects of modulators are small and disadvantageous effects will be more likely. Formic acid as modulator can slightly increase the BET surface area and pore volume of MIL-160 up to a modulator:linker ratio of 1.25 : 1. Acetic acid only shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Steinert et al recently showed that the addition of various monocarboxylic acids has no significant positive effect on the growth of Al-carboxylate MOFs (at least MIL-160) and attributed this to the relative inertness of such a cation. 96 Given that catecholate presents a stronger affinity for Al( iii ) than carboxylate, 97 this suggests that in addition to using modulators and ligands with similar binding strength as generally accepted, 50 this binding strength must be high enough to achieve a proper control of the crystal growth.…”
Section: Resultsmentioning
confidence: 99%
“…Steinert et al recently showed that the addition of various monocarboxylic acids has no significant positive effect on the growth of Al-carboxylate MOFs (at least MIL-160) and attributed this to the relative inertness of such a cation. 96 Given that catecholate presents a stronger affinity for Al( iii ) than carboxylate, 97 this suggests that in addition to using modulators and ligands with similar binding strength as generally accepted, 50 this binding strength must be high enough to achieve a proper control of the crystal growth.…”
Section: Resultsmentioning
confidence: 99%